KEANEKARAGAMAN TUMBUHAN BAWAH BERKHASIAT OBAT PADA TIGA TIPE VEGETASI DI KAWASAN STASIUN RISET KARANGSARI TAMAN NASIONAL GUNUNG CIREMAI - Anen, Nengsih; Sandi, Fakhri Dwi (Wana Raksa, 2023)
Research on the diversity of undergrowth species has been widely carried out in other places. However, at the Karangsari Research Station, Gunung Ciremai National Park, data on the diversity of types of undergrowth with medicinal efficacy is not yet available so the purpose of this study is to determine the types of undergrowth with medicinal efficacy and that dominate and the level of diversity in three types of vegetation (mixed forests, pine forests, thickets) in the Karangsari Research Station area of Gunung Ciremai National Park. This study used the area species curve method with data analysis using vegetation analysis, species diversity index, plant identification. Based on data analysis, it was shown that all the undergrowth found were identified as medicinally efficacious based on the literature and scientific foundations. For the number of types of medicinally efficacious undergrowth obtained 9 types in mixed forest vegetation, 12 types in pine forest vegetation, 20 types in shrub vegetation. The total types of medicinally efficacious undergrowth from all vegetation were obtained as many as 25 types from 18 families obtained from the results of sorting types in each cover because there are several types of the same in each cover. There are 4 types of undergrowth plants that can grow in three vegetation at the study site from 4 different families, namely Archery leaves (Ayapana triplinervis), Harendong (Clidemia hirta), Reeds (Imperata cylindrica), Bandotan (Ageratum conyzoides). This shows that types with relatively high abundance values are thought to be able to adjust to the surrounding situationPenelitian mengenai keanekaragaman jenis tumbuhan bawah telah banyak dilakukan di tempat lain. Akan tetapi di Stasiun Riset Karangsari Taman Nasional Gunung Ciremai data mengenai keanekaragaman jenis tumbuhan bawah berkhasiat obat belum tersedia sehingga tujuan penelitian ini adalah untuk mengetahui jenis tumbuhan bawah berkhasiat obat dan yang mendominasi serta tingkat keanekaragamannya pada tiga tipe vegetasi (hutan campuran, hutan pinus, senak belukar) di kawasan Stasiun Riset Karangsari Taman Nasional Gunung Ciremai. Penelitian ini menggunakan metode kurva spesies area dengan analisis data menggunakan analisis vegetasi, indeks keanekaragam jenis, identifikasi tumbuhan. Berdasarkan analisis data menunjukkan bahwa semua tumbuhan bawah yang ditemukan teridentifikasi berkhasiat obat berdasarkan literatur dan landasan ilmiah. Untuk jumlah jenis tumbuhan bawah berkhasiat obat diperoleh 9 jenis di vegetasi hutan campuran, 12 jenis di vegetasi hutan pinus, 20 jenis di vegetasi semak belukar. Adapun total jenis tumbuhan bawah berkhasiat obat dari seluruh vegetasi diperoleh sebanyak 25 jenis dari 18 famili diperoleh dari hasil pemilahan jenis di setiap tutupan karena ada beberapa jenis yang sama di setiap tutupannya. Terdapat 4 jenis tumbuhan bawah yang dapat tumbuh di tiga vegetasi pada lokasi penelitian dari 4 famili yang berbeda yaitu Daun panahan (Ayapana triplinervis), Harendong (Clidemia hirta), Alang-alang (Imperata cylindrica), Bandotan (Ageratum conyzoides). Hal ini menunjukan bahwa jenis-jenis dengan nilai kelimpahan relatif tinggi diduga mampu menyesuaikan dengan keadaan sekitar